Những câu hỏi liên quan
ND
Xem chi tiết
DM
Xem chi tiết
NK
27 tháng 12 2015 lúc 13:54

a = 2;b= (-2);c= 3

Thay : a+b+c=2+(-2)+3

                 .     =[2+(-2)]+3

                       =0+3=3

B)vì a và b là 2 số đối nhau nên ta có :

a =2;b= (-2) và là 2số đối nhau vì

|-2|=2

Bình luận (0)
FL
Xem chi tiết
ND
Xem chi tiết
TT
Xem chi tiết
DM
Xem chi tiết
TD
10 tháng 1 2016 lúc 8:55

a.M=a(b-c)+b(b-c)

M=(a+b)(b-c)

M=0(b-c)

M=0

 

Bình luận (0)
DM
Xem chi tiết
MH
27 tháng 12 2015 lúc 10:03

a. \(M=a.\left(b-c\right)+b.\left(b-c\right)=\left(b-c\right).\left(a+b\right)=\left(b-c\right).0=0\)

 

 

 

 

Bình luận (0)
DM
Xem chi tiết
SN
27 tháng 12 2015 lúc 10:19

ab-ac+b2-bc=ab+b2-(ac+bc)

=b(a+b)-(a+b)c

=b.0-c.0=0-0=0

Bình luận (0)
DT
Xem chi tiết